Human Endogenous Retroviruses Long Terminal Repeat Methylation, Transcription, and Protein Expression in Human Colon Cancer - Dolci, Maria; Favero, Chiara; Toumi, Wafa; Favi, Evaldo; Tarantini, Letizia; Signorini, Lucia; Basile, Giuseppe; Bollati, Valentina; D'Alessandro, Sarah; Bagnoli, Pietro; Ferrante, Pasquale; Delbue, Serena (Frontiers in Oncology, 2020)
Colon cancer is the fourth most common malignancy in both incidence and mortality in developed countries. Infectious agents are among the risk factors for colon cancer. Variations in human endogenous retrovirus (HERV) transcript and protein levels are associated with several types of cancers, but few studies address HERV expression in colon cancer. Fifty-eight patients with advanced-stage colon cancer were enrolled in this study. HERV-H, -K (HML-2), -P LTRs, Alu, LINE-1 methylation levels and transcription of HERV-H, -K (HML-2), and -P env and HERV-K pol genes in normal adjacent and tumor tissues were investigated by pyrosequencing and RT-qPCR, respectively. Expression of the HERV-K (HML-2) Pol and Env proteins in selected tissues was examined by Western blotting. Associations between HERV transcript expression and methylation levels and between clinical characteristics and HERV expression were evaluated. Compared to adjacent normal tissues, LINE-1 was hypomethylated in tumor tissues (p<0.05), whereas Alu, HERV-K (HML-2) and -H LTRs showed a decreasing trend in tumor tissue compared to normal tissue, though without a significant difference. The transcription levels of HERV env and pol genes were similar. However, the HERV-K (HML-2) Pol protein was more highly expressed (p<0.01) in surrounding normal tissues, but the HERV-K (HML-2) Env protein was only expressed in tumor tissues. Although HERV LTR methylation and gene expression did not show significant differences between tumor and normal tissues, HERV protein expression differed greatly. Pol protein expression in normal cells may induce reverse transcription and subsequent integration into the host genome, likely favoring cells transformation; in contrast, the Env protein in tumor tissue may contribute to cancer progression through cell to cell fusion.